High Altitude De-Acclimatization Syndrome (HADAS): A case report - Mishra, Rajesh Chandra; Mishra, Gaurav; Jahan, Ahsina; Debnath, Saurabh (Journal of Nepalese Society of Critical Care Medicine, 2024)
High Altitude De-acclimatization Syndrome (HADAS) is a clinical entity that arises when individuals return abruptly from high-altitude environments to lower altitudes without undergoing the necessary acclimatization processes. While altitude-related illnesses have been extensively studied, HADAS remains relatively underreported and may pose diagnostic challenges due to its varied and nonspecific clinical presentation. This case report aims to shed light on the importance of recognizing HADAS as a potential consequence of inadequate acclimatization, emphasizing the need for a thorough understanding of altitude-related disorders in individuals with a history of rapid altitude changes.